Simulasi Karakteristik Bubble Sebagai Indikasi Awal Terjadinya Fenomena Kavitasi Dengan Menggunakan Sinyal Vibrasi Pada Pompa Sentrifugal Dengan Menggunakan CFD (Computational Fluid Dynamic) - Rahman Rahman; Ikhwansyah Isranuri (e-Dinamis, 2012)
AbstractCavitation is one indication decline in pump performance. Indication of cavitation inpumps is the occurrence of high vibration and noise and damage to the pump impeller. Onecause of the vibration occurs is due to the emergence of bubble. In this research, observationwas done to determine the vibration characteristics and the characteristics of the bubble thatoccurred. After observing the characteristics of bubble that arisc by varying the capacity toobserve the flow patterns that occurred, then performed simulations using Computational FluidDynamics or CFD which aims to simulate the fluid flow in centripugal pumps performed byvarying its flow capacity. From the results of simulation that was done, the lowest pressure ofthe fluid in the impeller region continued to decline, namely, 6084.42 3745.33 Pa Pa, Pa3250.17, 524.53 Pa along with the smaller capacity of fluid flow. Along with the smaller capacityis also accompanied by increasing the top speed of fluid flow, namely, 27,62 m/s, 31,59 m/s,31,95 m/s, 75,76 m/s.Key words: Centrifugal, pump cavitation, suction pipe, pressure distribution, the distribution ofspeeds, the flow pattern.